Municipal documents (Spain). Procedure military in replacements of eighteenth and nineteenth centuries - Antonia Criado Lázaro (Documenta & Instrumenta, 2012)
Quintas records fill the shelves of Spanish municipal archives; while so far the study has been limited, or focused merginal in the second half of the twentieh century. In the present study provided the legislative basis of the procedure for Quintas in the military replacements eighteenth and nineteenth centuries and descrives some archival records belonging to these series Historical Documentary Heritage of the councils of Griñón and Torrelodones.